STRUCTURAL GLASS DESIGN ACCORDING TO CEN/TS 19100 - Osadchuk Т.; Demchyna Б.; Famuliak Ю.; Mykhailechko Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The work analyzes the existing regulatory documents on the design of structural glass. Due to the absence of approved standards, some provisions of the CEN/TS 19100 technical specifications and certain parts of the draft of the future Eurocode 10 (EN 19100) are considered. CEN/TS 19100 (prEN 19100) “Design of glass structures” consists of four parts: 1) Basis of design and materials; 2) Design of out-of-plane loaded glass components; 3) Design of in-plane loaded glass components and their mechanical joints; 4) Glass selection relating to the risk of human injury – Guidance for specification. In general, the European Committee for Standardisation (CEN) documents apply to the structural design of mechanically supported glass components and assemblies of glass components. They follow the principles and requirements of EN 1990 and cover the safety and serviceability of structures, the principles of their design and verification. CEN/TS 19100-1 (prEN 19100-1) describes the basic rules for the construction design of mechanically supported glass components. The document includes requirements for safety, load-bearing capacity, references to standards for different types of glass, glass strength and other properties. CEN/TS 19100-2 (prEN 19100-2) applies to the structural design of glass components loaded out of plane. The document includes provisions for the design of laterally loaded glass elements, calculation of laminated glass and insulating glass units. CEN/TS 19100-3 (prEN 19100-3) applies to the structural design of in-plane loaded glass components. CEN/TS 19100-4 deals with provisions relating to the risk of human injury and guidelines for glass specification.